M-N Interaction Diagrams of RC Columns Strengthened with Steel C-Sections and Battens - Hamza M. Salman; Mohannad H. Al-Sherrawi (Civil Engineering Journal, 2024)
Due to design errors and changes in the use of buildings, reinforced concrete (RC) columns must often be strengthened to support additional live loads. The column must be designed to withstand both axial loads and bending moments, and an interaction diagram is necessary to demonstrate the column failure. The most common technique for strengthening RC columns uses a steel jacket consisting of four steel angles and battens. In this study, another strengthening technique was proposed that uses two steel C-sections with steel battens. A new approach for constructing an axial force-bending moment interaction diagram for RC columns strengthened with steel C-section jackets using an analytical model based on the plastic stress distribution method was introduced. A finite element (FE) model was created using Abaqus software, and the FE results were consistent with the experimental and analytical results. The analytical and FE results showed that this strengthening method was effective and increased the axial load and bending moment capacities of the strengthened columns. This increase was explained by the confining effect of the steel jacket and the ability of the steel C-sections to withstand a large part of the applied load. This approach offers an effective and economical solution for the reinforcement of RC columns and provides a reliable and safe option for structural engineers. Doi: 10.28991/CEJ-2024-010-06-016 Full Text: PDF